The Association Between Mode of Delivery and Later Educational Outcomes - Li, Eileen; Slykerman, Rebecca; Milne, Barry (International Journal of Population Data Science, 2020)
Introduction Caesarean section (C-section) is becoming increasingly prevalent worldwide. It can be a life-saving intervention when medical complications arise, but may cause adverse consequences for the mothers when it is not medically necessary. The upwards trend of C-section is becoming a general concern as it might be associated with a wide range of child outcomes such as immune diseases, respiratory diseases and developmental problems. One underlying mechanism of such association is through gut microbiota. Mode of delivery is a signification factor which determines the gut bacterial environment in early days of life. Gut microbiota can impact cognitive development via microbiota gut brain axis. Objectives and Approach This study investigated the association between mode of delivery and later educational outcomes of the children, using linked data from New Zealand Integrated Data Infrastructure. The participants consisted of children born in New Zealand between 1Jan1996 and 31Dec1998. All birth information were retrieved from Department of Internal Affairs and were linked to Ministry of Health data to obtain delivery methods from mothers’ diagnosis records. Once delivery modes were identified, the data was then linked to records from Ministry of Education to obtain children’s educational outcomes at secondary school. Three outcome variables were chosen: University Entrance, Highest Endorsement Level and National Certificate of Educational Achievement Level 2 Percentile Score. Results The results have shown that C-section and assisted vaginal delivery were associated with better secondary school educational achievement, comparing to unassisted vaginal delivery. The results persisted after adjusting for sociodemographic factors such as household income, maternal education and deprivation index; infant factors such as birth weight, gestational age and ethnicity. However, when within family variation was further controlled for in the sibling fixed effects analysis, C-section was no longer associated with improved educational achievement. Conclusion / Implications This indicated that the impact of delivery mode might be negligible on later educational achievement.